2015
DOI: 10.1080/09603123.2014.1003038
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization ofVibrio vulnificusstrains isolated from oyster samples in Mexico

Abstract: Vibrio vulnificus strains were isolated from oysters that were collected at the main seafood market in Mexico City. Strains were characterized with regard to vvhA, vcg genotype, PFGE, multilocus sequence typing (MLST), and rtxA1. Analyses included a comparison with rtxA1 reference sequences. Environmental (vcgE) and clinical (vcgC) genotypes were isolated at nearly equal percentages. PFGE had high heterogeneity, but the strains clustered by vcgE or vcgC genotype. Select housekeeping genes for MLST and primers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…This result is similar to that of a study recording a significantly higher percent of the E-genotype of V. vulnificus isolates recovered from oysters [ 56 ]. Although such a result is expected from environmental samples, it is, however, contrary to a report where nearly an equal percent of vcgE (47%) and vcgC (53%) were detected from oyster isolates [ 57 ] and water areas surrounding oyster harvest [ 56 ]. Continuous monitoring of seafood and fish products remains a necessity as infection with V. vulnificus , although rare, is usually fatal, particularly in immunocompromised persons.…”
Section: Discussioncontrasting
confidence: 77%
“…This result is similar to that of a study recording a significantly higher percent of the E-genotype of V. vulnificus isolates recovered from oysters [ 56 ]. Although such a result is expected from environmental samples, it is, however, contrary to a report where nearly an equal percent of vcgE (47%) and vcgC (53%) were detected from oyster isolates [ 57 ] and water areas surrounding oyster harvest [ 56 ]. Continuous monitoring of seafood and fish products remains a necessity as infection with V. vulnificus , although rare, is usually fatal, particularly in immunocompromised persons.…”
Section: Discussioncontrasting
confidence: 77%
“…vulnificus strains does not necessarily correspond to their clinical or environmental isolation. Guerrero et al [8], have reported close homology between environmental isolates of C-genotype strains by PFGE, MLST, and rtxA1 analysis, in which V . vulnificus C-genotype strains from oysters clustered with C-type rtxA1 V .…”
Section: Discussionmentioning
confidence: 99%
“…We have compared the whole-genome sequences of 2 V . vulnificus strains from oyster samples that have been studied by Guerrero et al [8]—CICESE-316 and CICESE-325 (MLST lineage I, C-genotype, rtxA1 -C type)—with 2 reference genomes of the V . vulnificus strains CMCP6 and YJ016 (MLST lineage I, C-genotype, rtxA1 -C type), which have been reported to be acute human pathogens (Genbank Accession Numbers AE016795.3, AE016796.2, and BA000037.2, BA000038.2, respectively) and examined by several groups [22, 23, 2628].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations